The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1155/2009/693794
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Lactose Digestion Status on Baseline Fecal Microflora

Abstract: The differential bacterial effects of lactose were not quantitatively detected in stool samples taken in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In the present study, we did not analyze the microbiota composition of the fecal samples as we hypothesized that differences in microbiota composition might explain differences in metabolite production but would not directly explain complaints. In addition, previous studies have already indicated that the microbiota composition did not differ between tolerant and intolerant subjects with lactose malabsorption [ 7 ] nor between subjects with normal lactose digestion and subjects with lactose malabsorption [ 30 ]. Nevertheless, it cannot be excluded that the bacterial techniques used in these studies (fluorescent in situ hybridization (FISH) and bacterial counting after plating, respectively) were not sensitive enough to detect subtle differences in microbiota composition and that current state-of-the-art techniques like next generation sequencing might be more informative.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we did not analyze the microbiota composition of the fecal samples as we hypothesized that differences in microbiota composition might explain differences in metabolite production but would not directly explain complaints. In addition, previous studies have already indicated that the microbiota composition did not differ between tolerant and intolerant subjects with lactose malabsorption [ 7 ] nor between subjects with normal lactose digestion and subjects with lactose malabsorption [ 30 ]. Nevertheless, it cannot be excluded that the bacterial techniques used in these studies (fluorescent in situ hybridization (FISH) and bacterial counting after plating, respectively) were not sensitive enough to detect subtle differences in microbiota composition and that current state-of-the-art techniques like next generation sequencing might be more informative.…”
Section: Discussionmentioning
confidence: 99%
“…From these, we identified 74 further restricted publications, which appeared more relevant but 48 were excluded because they did not compare genetics with the targeted indirect tests, leaving 26. Among these 21 dealt with LBHT (three examined both LBHT and LTT), three dealt with LTT exclusively, and two with potential polymorphisms other than the C/T or G/A types 12, 16, 17, 30–52 …”
Section: Resultsmentioning
confidence: 99%
“…Two of these 10 specifically targeted patients with diagnosis of functional bowel disorders 36, 43 and one selected men at random for comparisons 30 . In the case of the other nine studies, all were volunteers and most were recruited: one study selected random volunteers from hospital out‐patient clinics, 34 seven studies included symptomatic volunteers, one specifically with irritable bowel syndrome 35 and two included volunteers with only self‐reported lactose intolerance 12, 41 . All except the study of Nagy et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of the largest studies conducted to assess concordance between indirect methods for evaluating lactose malabsorption (HBT and LTT) [7,15,17]. Concordance between HBT and LTT was moderate, which may be due to the fact that HBT depends on colonic flora [18], whereas LTT is influenced by physiologic response to glucose. However, concordance between the two tests improved when the LTT cut-off was set at 15 mg/dL in LTT.…”
Section: Discussionmentioning
confidence: 98%